Hubungan keyakinan mahasiswa calon guru terhadap kemampuan merancang pembelajaran matematika selama perkuliahan daring - Noviartati, Kurnia; Ernawati, Agustin (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
STKIP Al Hikmah as teachers school has seriously faced the spread of Coronavirus disease 2019 (Covid-19) by conducting online learning. This article aims to describe the relationship of prospective teachers’ belief to their ability on designing mathematics learning during online learning in this global pandemic. This is qualitative research using an online questionnaire and students’ design on mathematics learning as data. This result shows that five of seven prospective teachers’ belief has linear relationship to their ability on designing mathematics learning during online learning while others non-linear. This linear relationship is supported by either high students’ belief and good instructional design or medium students’ belief and instructional design. While the non-linear is supported by low students’ belief and weak instructional design.